The Professional Socialization of Certified Athletic Trainers in High School Settings: A Grounded Theory Investigation - Pitney, William A. (National Athletic Trainers Association, 2002)
Objective: To gain an understanding of the professional socialization experiences of certified athletic trainers (ATCs) working in the high school setting. Design and Setting: A qualitative investigation using a grounded theory approach was conducted to explore the experiences related to how ATCs learned their professional role in the high school setting. Participants: A total of 15 individuals (12 ATCs currently practicing at the high school level, 2 current high school athletic directors who are also ATCs, and 1 former high school ATC) participated in the study. The average number of years in their current position for the 12 currently practicing ATCs was 10.16 ± 7.44, with a range of 2 to 25 years. The 2 athletic directors averaged 5.5 years of experience in their roles, and the former high school athletic trainer had worked in that setting for 1 academic year. Data Analysis: The interviews were transcribed and then analyzed using open, axial, and selective coding. Peer debriefing, member checks, and triangulation were used to establish the trustworthiness of the study. Results: Informal learning processes were discovered as the overarching theme. This overarching theme was constructed from 2 thematic categories that emerged from the investigation: (1) an informal induction process: aspects of organizational learning, and (2) creating networks for learning. Conclusions: Informal learning is critical to the professional socialization process of ATCs working in the high school setting. Because informal learning hinges on self-direction, self-evaluation, reflection, and critical thinking, the findings of this study indicate that both preservice and continuing education should attempt to foster and enhance these qualities.